Effectiveness of testosterone replacement in men with obesity: a systematic review and meta-analysis - Mangolim, Amanda Sampaio [UNESP]; Brito, Leonardo de Andrade Rodrigues [UNESP]; Nunes-Nogueira, Vania Dos Santos [UNESP] (Oxford University Press (OUP), 2021)
Objective: This systematic review evaluated the effect of testosterone replacement therapy (TRT) in men with obesity having low testosterone levels (LTLs). Design and methods: Search strategies were performed in MEDLINE, Embase, LILACS, and CENTRAL databases. Two reviewers selected the studies, assessed the risk of bias, and extracted data from the included studies. A random-effects model was used to pool results across studies, and the Grading of Recommendations Assessment, Development, and Evaluation was used to evaluate the certainty of evidence. Results: A total of 16 randomized controlled trials were included. With moderate certainty of the evidence, no difference was found between TRT and placebo regarding total adverse events, TRT led to a 2-kg lean body mass gain and slightly improved low-density lipoprotein (LDL), without effects on the blood pressure. Due to imprecision/heterogeneity, effects in cardiovascular events (relative risk: 0.52, 95% CI: 0.26 to 1.05, 7 trials, 583 participants), high-density lipoprotein, hematocrit, prostate-specific antigen, HbA1c, and quality of life were unclear. TRT was effective for waist circumference and BMI; however, large between-study heterogeneity was found, with 95% prediction intervals crossing the null effect line. Meta-regression revealed that the average age of participants was a significant modifier for both outcomes. Conclusion: TRT slightly improved the lean body mass and LDL in men with obesity having LTLs but did not affect the blood pressure. The effects of TRT on cardiovascular events, HbA1c, and quality of life are unclear. The mean age of participants significantly modified the effect of TRT on weight loss.